Evaluation of Lathe Operating Conditions Based on ISO 10816 Using the Correlation Between Spindle Vibration and Surface Quality - Talifatim Machfuroh; Zakiyah Amalia; Siti Duratun Nasiqiati Rosady; Nurlia Pramita Sari; Agus Hardjito; Subagiyo (Logic : Jurnal Rancang Bangun dan Teknologi, 2026)
The evaluation of machine tool operating conditions is commonly performed based on mechanical reliability, while its direct relationship with the quality of machined surfaces is still rarely quantified. This study aims to evaluate the operating condition of a conventional lathe based on ISO 10816 by analyzing the correlation between spindle vibration and surface roughness. Experiments were conducted on a Dixon CQ6236X1000 lathe with variations in feed rate (0.104–0.835 mm/rev) and depth of cut (0–1.5 mm) at a constant spindle speed of 460 rpm. Spindle vibration was measured in terms of root mean square (RMS) velocity (mm/s) in the vertical and horizontal directions, and frequency-domain analysis was performed using Fast Fourier Transform (FFT). Surface roughness was evaluated using Ra, Rq, and Rz parameters. The results show that the RMS vibration values range from 0.4 to 2.5 mm/s, which correspond to Zone B and Zone C of ISO 10816-3 class I. At Zone B, the surface roughness values are relatively low (Ra = 2–6 µm), indicating stable machining conditions. However, when the operating condition shifts to Zone C, the surface roughness increases significantly, with Ra values exceeding 10 µm under certain cutting conditions. The correlation analysis between RMS vibration and surface roughness yields a coefficient of determination of R² = 0.399, indicating a moderate positive relationship. FFT analysis reveals that the dominant vibration components are associated with spindle rotational frequency and its harmonics, indicating the presence of mild regenerative chatter without evidence of bearing defects.These findings demonstrate that ISO 10816 can be utilized not only as a mechanical acceptability standard but also as a predictive indicator of surface quality in turning operations. The results provide a useful reference for integrating vibration-based condition monitoring with machining quality control in both industrial and educational workshop environments.